Evaluation of medication package inserts in Saudi Arabia - Al-aqeel, Sinaa A (Dove Medical Press, 2012)
PURPOSE: The aim of this study was to examine if package inserts (PIs) supplied with prescribed and over-the-counter medications in Saudi Arabia contain information relevant for the safe and appropriate use of these medications. METHODS: Sixty PIs for prescription-only medications (n = 37) and over-the-counter medications (n = 23) were evaluated against a set of safety criteria compiled from the literature. RESULTS: Analyzed PIs were defective in many aspects. Particularly of concern were unclear dosage instructions, lack of measures to be taken when an administrative error was made, inappropriate presentation of side effects, and lack of measures to be taken if serious side effects occurred. CONCLUSION: This study indicated that information relevant to the safe and appropriate use of medications was not uniformly mentioned in the PIs analyzed. To avoid medication errors due to deficits in the current PIs, we recommend improvement in the existing PIs based on best practice for information content and design.